Correlating drug release with microstructure of hydrogel-based delivery systems - Prasittisart, Pundarik (2020)
Hydrogels are three-dimensional networks of polymers which can absorb a large amount of water. They have been utilised in pharmaceutical and biomedical applications ranging from an established application in oral dosage tablets to more recent use in regenerative medicines. The use of hydrogels for oral sustained drug delivery has been demonstrated in numerous previous studies where hydroxypropyl methylcellulose (HPMC) was employed to reduce dosing frequency, thereby improving patient compliance. In previous research the focus of HPMC studies was limited to its effects on drug release. Injectable hydrogels have recently received increased attention as potential tissue regeneration platforms. Due to their high water content, hydrogels can be used to replicate the microenvironment of the cartilage extracellular matrix. In both systems, however, the correlation of formulation variables and release performance is still poorly understood. The current research aims to provide insight into the release mechanism of active substances from two hydrogel-based delivery systems, tablets and injectable hydrogels, using chemical and electron imaging techniques. A series of caffeine tablets containing various amounts of HPMC and particle size fractions were produced and cross-sectioned. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) was used to analyse the caffeine tablets and their raw materials. ToF-SIMS successfully distinguished key components and revealed the characteristics of compressed ingredients in tablets. Changing HPMC factors significantly affected the microstructure of the tablets. The inter-particle distance and intersection counts of HPMC were proved to be indicative of HPMC’s role in developing gel layers during the early dissolution periods (< 60 minutes). Prediction of caffeine release from the HPMC matrix tablets was made with the maximum error of less than 5 %. Using ToF-SIMS, the interconnectivity of HPMC networks in 30 %w/w HPMC tablet matrices was evident which is in agreement with percolation theory. This work additionally conducted an examination of microstructural changes to the polymer concentration after exposure to water. After 15 minutes dissolution, the gel layer was completely formed in the 30 %w/w HPMC tablets, whereas, the incomplete gel layer was found when using 15 %w/w HPMC. The caffeine particles were only retained in the core of the tablets with the complete gel layer functioning as a depot for sustained drug release. Considerable insight has been gained to elucidate the release performance of drug from HPMC matrix tablets which might be useful for improving knowledge about the performance of other extended release systems. In the case of injectable hydrogels, the incorporation of human platelet lysate (PL) was investigated relating to the application of hydrogels for protein delivery in cartilage regeneration. In situ forming hydrogels composed of hyaluronic acid-tyramine (HA-TA) and dextran tyramine (Dex-TA) were prepared by an enzymatically crosslinking reaction with horseradish peroxidase and H2O2. The gels have been optimised by varying the concentration of HA-TA and Dex-TA, H2O2/TA molar ratio and PL/PBS ratio to obtain fast gelation time, good handleability and good mechanical properties of the gels. The Dex-TA gels exhibited faster protein release than the HA-TA gel. Cryo-focused ion beam scanning electron microscopy and a sublimation technique were used to obtain and image the internal structure of hydrogels by preserving them close to their native hydrated state. The ultrastructure of the gels was found to be related to the release rate of proteins. The faster release of growth factors and cytokines from the Dex-TA gels can be explained by the higher porosity and larger pores of the Dex-TA gels. On the other hand, the pores of the HA-TA gels were found to be uniformly smaller which may lead to the more delayed release of proteins. This research has investigated the formulation-structure-release relationship of hydrophilic matrices and in situ forming injectable hydrogels. Based on this knowledge, future work may focus on designing hydrogel-based delivery systems and tailoring drug release. Therefore, it could offer significant development for effective formulation designs.